(untitled) (Research, Society and Development, 2020)
Self-esteem is defined as a construction of opinions that human beings have about their own body image. It is an integrative literature review. To guide this study, the following non-clinical question (PICo) was asked: How did the diabetic patient’s self-esteem interfere in the healing process of foot injuries? Data collection was performed through electronic search in the period of June 2020 in the following databases: Bireme (Virtual Health Library - VHL), PubMed of the National Library of Medicine and CINAHL (Cumulative Index to Nursing and Allied Health Literature). 6 articles were selected for this Review. Most studies dealt with the self-esteem of diabetics in the healing process of the foot injury, in which the studies showed the feelings of diabetics regarding their current health condition, where fear, anxiety, low stigma, disability, melancholy, embarrassment, concerns and sadness were feelings cited by patients as a result of injuries to the feet of diabetics, causing changes in self-esteem and self-image. Changes in emotions, quality of life and functional capacity, qualification of health professionals, glycemic counseling and psychological support are fundamental in the face of the healing process, in addition to patient feedback, a factor that is necessary to obtain a positive result.